Counseling Model Design in Optimization Learning the Qur'an - Nurlaila Nurlaila (Fitrah, 2026)
Learning the Qur'an plays a role role crucial in Islamic education, no only in increase skills reading and memorizing, but also deep form character and spirituality students . However , various challenge like low motivation, difficulties in understand text, and obstacles psychological often hinder effectiveness of the learning process. This study aim For designing a counseling model systematically to optimize learning the Qur'an in institutions Islamic education. The methods used is review literature that analyzes theory and research relevant about integration counseling in Islamic education. Findings show that counseling model consists of from three stage Main : (1) Initial Assessment , which identifies obstacle Study students, (2) Assistance Based Counseling, which applies technique like listening, empathy, reflection, and exploration For increase motivation and understanding student towards the Qur'an, and (3) Evaluation Sustainable, which involves monitoring progress and adjustment of intervention strategies If required. This model recommended as approach holistic For increase effectiveness learning the Qur’an and can implemented in institutions Islamic education.